Using AphasiaBank for Discourse Assessment - Fromm, Davida; Forbes, Margaret; Holland, Audrey; MacWhinney, Brian (Seminars in Speech and Language, 2020)
AphasiaBank is a shared, multimedia database for the study of communication in aphasia. This article describes a variety of discourse measurement tools and teaching resources available at the AphasiaBank website. The discourse measurement tools include main concept analysis, core lexicon checklists, correct information unit computation techniques, and other automated analyses using the CLAN program. These tools can be used to measure a variety of aspects of language production for assessment as well as treatment evaluation and clinical research purposes. Importantly, they are intended to help make the discourse analysis process more efficient and reliable. Teaching resources include an online tutorial on aphasia, videos of typical behaviors seen in aphasia, group treatment videos, classroom activities, tutorial screencasts, and conference posters. These resources can be used for a variety of clinical and educational purposes. The AphasiaBank website is part of the larger TalkBank project which provides many other shared databases and resources that are relevant to professionals interested in communication and communication disorders.
Keywords: Aphasia; discourse; CHAT; CLAN